Association between cognitive impairment and criteria for frailty syndrome among older adults - Allan Gustavo BRIGOLA; Ana Carolina OTTAVIANI; Danilo Henrique Trevisan CARVALHO; Nathalia Alves OLIVEIRA; Érica Nestor SOUZA; Sofia Cristina Iost PAVARINI (Arquivos de Neuro-Psiquiatria)
Abstract The association between cognitive impairment and physical frailty has been studied in older adults. The criteria degree of frailty may be keys to associated cognitive impairment. Objective: To analyze the association between cognitive impairment and the criteria for frailty. Methods: We cross-sectionally examined data from 667 older adults (≥60 years of age) from a study entitled ‘Variables associated to cognition in elderly caregivers’ involving patients in an urban and rural primary healthcare center. We defined cognitive impairment based on different groups of scores on the Mini Mental State Examination, and defined frailty and prefrailty using the criteria by the Cardiovascular Health Study. We performed multinomial regression models to analyze the association between levels of frailty and cognitive impairment. Results: Similar proportions of women (54.8%) and men (45.2%) participated in the study (mean age: 71 years old). We found cognitive impairment, prefrailty and frailty in 34, 54, and 24% of the participants, respectively. Concomitant cognitive impairment and frailty was found in 13% of them. The chances of cognitive impairment increased up to 330% (Odds Ratio [OR]: 4.3; 95% confidence interval [95%CI] 2.4‒7.7; p<0.001) among frail individuals, and 70% (OR: 1.7; 95%CI 1.0‒2.8; p=0.033) among prefrail individuals compared to robust/non-frail individuals. After controlling for age, education, place of residence and functional dependence, slowness and fatigue criteria were significantly associated with cognitive impairment. Conclusion: Older adults with frailty have a greater likelihood of concomitant cognitive impairment than prefrail and robust older adults. The prevalence of cognitive impairment and frailty is consistent with data reported in literature. The present findings contribute to the investigation of cognitive frailty.